Weasel of the week "Settle a native lands claim after only 136 years? Whoa Nellie - Why the rush!?!" - Murphy, Dan (The Province, 1996)
Weasel of the week "Settle a native lands claim after only 136 years? Whoa Nellie - Why the rush!?!"